Correction: Phosphorescent bio-based resin for digital light processing (DLP) 3D-printing. Issue 21 (16th October 2020) - Maturi, Mirko; Pulignani, Carolina; Locatelli, Erica; Vetri Buratti, Veronica; Tortorella, Silvia; Sambri, Letizia; Comes Franchini, Mauro
Abstract : Correction for 'Phosphorescent bio-based resin for digital light processing (DLP) 3D-printing' by Mirko Maturi et al., Green Chem., 2020, 22, 6212–6224, DOI: ; 10.1039/D0GC01983F .